Las experiencias de aprendizaje y su influencia en la discriminación sensorial en niños de 3 años de la unidad educativa liceo cristiano de Guayaquil en el año lectivo 2017 - Arauz Astudillo, Lissette Samira (2018)
It has been considered pertinent to carry out this present work because it consists of knowing the limitation in sensory discrimination presented by the 3-year-old children of the Unidad Educativa Liceo Cristiano de Guayaquil, in order to achieve the above described, it has been decided to choose descriptive research, as it will provide the collection of data and thus to know in depth the problematic of the object under study, its strengths and weaknesses to face the challenge. It is important to know the advantages and disadvantages of the sensory limitation and what consequences it may have in the school stage; Its main objective is to achieve the development of sensory discrimination of children through the senses through learning experiences, this will allow sensory maturity, lasting and significant knowledge; also obtain the foundations for the cognitive and perceptual development……….